The blast resistant performance of concrete-filled steel-tube segmental columns - Zhang, Xihong; Hao, Hong; Li, M.; Zong, Z.; Bruechert, J.W. (ELSEVIER SCI LTD, 2020)
Prefabricated segmental concrete column has seen an increased rate of adoption in the construction industry. Much effort has been paid to investigate the performance of segmental column under seismic and impact loadings. The study of its blast resistant performance is very limited. In the meanwhile, field blast tests and numerical simulations have demonstrated that concrete-filled steel-tube (CFST) columns exhibit outstanding blast resistant capacity. This study aims to investigate the blast performance of segmental column with CFST segments. A detailed 3D model of segmental CFST columns are generated using LS-DYNA. The model is validated with field blast testing data on CFST column and laboratory impact test on segmental column. The blast resistant performance of segmental CFST column is compared with conventional monolithic column and monolithic column with prestress. Parametric study is then conducted to investigate the influences of infill concrete strength, steel skin thickness, pre-stress ratio, and number of segments on the blast resistance of the segmental column. It is found that increasing the steel skin thickness could most effectively improve the blast resistance of a segmental CFST column, while increasing the concrete strength, prestress force, and the number of segments, also improve the capacity of segmental CFST column to resist blast loading.